2009
DOI: 10.1007/s10895-009-0557-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Spiro-Oxazino-Quinoline Derivatives and Study of Their Photophysical Properties

Abstract: A convenient route was successfully developed for the synthesis of novel heterocycles such as spiro-oxazino-quinoline derivatives from 2-aminoquinoline-3-carbonitrile (4) in good yield. The Spiro-quinoline derivatives (6, 8 and 10) were synthesized and further studied for their photophysical properties. Semiempirical molecular orbital calculation (PM3/PM6 for structure) proves to be a suitable tool for the prediction of absorption and fluorescence properties of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…From literature it was also noted that 1,8-naphthyridine derivatives were not only use as luminescence materials in molecular recognition because of their rigid planer structure [6][7][8], possess antibacterial [9], antymicobacterial [10], antitumoral [11], anti-inflammatory [12], antiplatelet [13], gastric antisecretary [14], antiallergic [15] and local anaesthetic [16]. Recently, our research group reported systematic studies about the fluorescence properties of differently substituted pyrazolofused heterocycles [17][18][19][20][21][22] and benzo naphthyridines [23][24][25][26]. Annulation reactions with hetrocyclic aminoaldehydes provides synthectic entry into hetrocyclic systems, fused to a pyridine or pyrimidine nucleus by Friedlander condensation reactions with reactive methylenes.…”
Section: Introductionmentioning
confidence: 99%
“…From literature it was also noted that 1,8-naphthyridine derivatives were not only use as luminescence materials in molecular recognition because of their rigid planer structure [6][7][8], possess antibacterial [9], antymicobacterial [10], antitumoral [11], anti-inflammatory [12], antiplatelet [13], gastric antisecretary [14], antiallergic [15] and local anaesthetic [16]. Recently, our research group reported systematic studies about the fluorescence properties of differently substituted pyrazolofused heterocycles [17][18][19][20][21][22] and benzo naphthyridines [23][24][25][26]. Annulation reactions with hetrocyclic aminoaldehydes provides synthectic entry into hetrocyclic systems, fused to a pyridine or pyrimidine nucleus by Friedlander condensation reactions with reactive methylenes.…”
Section: Introductionmentioning
confidence: 99%
“…Several naturally occurring drug molecules contain quinoline rings as their constituents . Aminoquinoline derivatives are useful in cyclisation reactions for ring expansion and for the synthesis of steroids . Multiple possibilities exist to obtain cyclised products from intramolecular cyclisation reactions of 8‐aminoquinoline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolines, coumarins and fluorenes are well‐known fluorescent compounds of high quantum yield and have attracted much attention in current research because of their interesting electronic and photophysical properties [7–10] and potential high technology applications, including fluorescence probes in chemosensors [11–13], organic electro‐luminescence devices (OLEDs) [14–16], organic photovoltaic cells (OPVs) [17,18] and two‐photon absorption (TPA) materials [19,20]. Furthermore, fluorene‐based compounds show a large π‐electron conjugated surface with extensive electron delocalisation.…”
Section: Introductionmentioning
confidence: 99%